2018
DOI: 10.3389/fncel.2018.00373
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds Characteristic of the Mediterranean Diet in Mitigating Microglia-Mediated Neuroinflammation

Abstract: Neuroinflammation is a pathological feature of quite a number of Central Nervous System diseases such as Alzheimer and Parkinson’s disease among others. The hallmark of brain neuroinflammation is the activation of microglia, which are the immune resident cells in the brain and represents the first line of defense when injury or disease occur. Microglial activated cells can adopt different phenotypes to carry out its diverse functions. Thus, the shift into pro-inflammatory/neurotoxic or anti-inflammatory/neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 241 publications
(281 reference statements)
1
88
0
1
Order By: Relevance
“…Previous studies have shown the antioxidant and anti-inflammatory properties of HT in several models of human diseases, such as rheumatoid arthritis, hepatic and intestinal inflammation, diabetes, glioma, and osteoarthritis, among others [34]. In vitro studies have also revealed the anti-inflammatory effects of HT in monocytes/macrophages and point out some of its possible mechanism of action [17][18][19]. However, the possible anti-inflammatory properties of HT in microglia, the main immune cells in the CNS, have remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the antioxidant and anti-inflammatory properties of HT in several models of human diseases, such as rheumatoid arthritis, hepatic and intestinal inflammation, diabetes, glioma, and osteoarthritis, among others [34]. In vitro studies have also revealed the anti-inflammatory effects of HT in monocytes/macrophages and point out some of its possible mechanism of action [17][18][19]. However, the possible anti-inflammatory properties of HT in microglia, the main immune cells in the CNS, have remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory activity of HT has been previously tested on macrophage cell lines, with the TLR-4 ligand lipopolysaccharide (LPS) as a stimulating agent, and proved that HT diminished the secretion of cytokines induced by LPS, including IL-1α, IL-1β, IL-6, IL-12, and TNF-α, as well as chemokines, such as C-X-C motif chemokine 10 (CXCL10/IP-10) and monocyte chemoattractant protein 1 (MCP-1/CCL2), through a mechanism non-dependent on the NF-κB signaling pathway [17][18][19]. Another recent study has proved that HT in LPS-treated RAW264.7 cells modulates oxidative stress by the involvement of nuclear factor erythroid 2-related factor 2 (Nrf2) [20].…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] In fact, HTyr reduces oxidative stress in brain slices undergoing such stress, that is, lipid peroxidation, peroxynitrite formation, and production of inflammatory mediators (prostaglandin E2 and interleukin 1beta) 27 ; similarly, HTyr protects in vitro from oxidative stress, by rescuing either PC12 cells or SH-SY5Y neuroblastoma cells from 6-hydroxydopamine-induced damage, from L-DOPA toxicity or preventing hydrogen peroxide-induced death. [28][29][30] Moreover, HTyr is able to cross the blood-brain barrier 31,32 and its treatment in a mouse model of Alzheimer's disease (TgCRND8 mice) caused a significant reduction of the amyloid-β plaque number in hippocampal areas. 33 However, despite the extensive literature about the modulation of adult neurogenesis by several phenolic compounds (34,35, for review), little is known about the potential role of HTyr in this process in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic neurodegenerative diseases are untreatable and few approved synthetic drugs reduced adverse symptoms but not cure them. In this discouraging scenario, oral supplementation with vegetal bioactive derivatives or the Mediterranean diet are promising to postpone the irreversible progression of AD, PD, ALS, FTD (Vauzour et al, 2017;Hornedo-Ortega et al, 2018;Pohl and Lin, 2018;Fernandez-Sanz et al, 2019).…”
Section: Nutraceuticals Effective In Neurodegeneration Via Autophagymentioning
confidence: 99%